Respon Pertumbuhan dan Hasil Tanaman Bayam terhadap Aplikasi Ecoenzyme Berbahan Dasar Limbah Pertanian Lokal Banyuwangi - Ari Istanti; Aldy Bahaduri Indraloka; Sari Wiji Utami; Riska Ardianti; Selvi Nur Dinah; Veronica Nafa Urridha (AgriMalS, 2026)
Ecoenzyme (EE) is a fermented liquid derived from organic fruit and vegetable waste that has the potential to enhance plant growth and support sustainable agriculture. This study aimed to evaluate the effect of different organic waste-based Ecoenzyme formulations on the growth of spinach plants. The experiment was conducted using a pot experiment arranged in a Completely Randomized Design (CRD) consisting of four treatments: P1 (mustard greens + mangosteen peel), P2 (mustard greens + orange peel), P3 (mustard greens + dragon fruit peel), and P4 (mustard greens only). The observed growth parameters included plant height, leaf number, fresh weight, and total chlorophyll content. The results showed that Ecoenzyme application significantly affected plant height and fresh weight, while the number of leaves did not differ significantly among treatments. These findings indicate that Ecoenzyme produced from a combination of vegetable and fruit organic wastes has the potential to be utilized as an alternative liquid organic fertilizer to support spinach cultivation.